The Role of Bi’ah Lughawiyyah in Enhancing Arabic Language Proficiency: A Systematic Literature Review - Nimas Nurul Halimah; Hidayatuzzainiyah; Asfiya Ullayali; Ilmiyanti; Dini Islamiyatul Asri; Muhammad Zubair; Abdul Hayyi Syarifullah (Formad English Foundation NTB Jakarta, 2026)
Arabic language learning often faces significant challenges in transforming theoretical mastery into active communication skills. One of the central factors determining the success of language acquisition is the existence of bi’ah lughawiyyah (language environment) as a social laboratory for students. This study aims to deeply examine the role of bi’ah lughawiyyah and analyze its effectiveness in improving students’ Arabic language competence. The research method employed is a Systematic Literature Review (SLR) by reviewing various relevant scientific articles published between 2016 and 2025. The results indicate that bi’ah lughawiyyah is proven effective in improving Arabic language skills, demonstrated by an increase in verbal proficiency (mahārah kalām) with a significant contribution in the moderate category between 28.5% and 32.9%. The implementation of habituation strategies, vocabulary labeling, and multimedia support creates a conducive learning atmosphere, reduces language anxiety, and builds students’ self-confidence. The success of this ecosystem is influenced by internal factors such as student motivation, and external factors including managerial policies, teacher qualifications, and integrative environmental design. Thus, strengthening bi’ah lughawiyyah is recommended as an essential strategy to reconstruct Arabic language learning from a mere academic burden into a functional and productive social practice.